Difficulties of the slow learner in reading skill: Sekolah Rendah Agama Paya Jaras Sungai Buloh - Abd Khalid, Siti Nur Aisyah; Mohd Ismath, Nurul Hanilah (Kulliyyah of Languages and Management, International Islamic University Malaysia, Pagoh Campus, 2019)
يسعى هذا البحث إلى اكتشاف صعوبات المتعلم البطيء في مهارة القراءة باللغة العربية لدى طلبة المدرسة الابتدائية، كما أنها تهدف إلى الطرق للتغلب على هذه المشكلة. وتمّ اختيار الباحثة المدرسة الابتدائية الدينية فايا جارس سوغاي بولوه لاكتشاف المتعلم البطيء في منطقة ريفية تقع خارج المدن والبلدات. ويتبع هذا البحث المنهج الوصفي والتحليلي لدراسة الواقع التعليمي. فتشتمل عينة هذا البحث على كل المعلمين الماليزيين الذين يعلمون الطلبة في المدرسة الابتدائية الدينية فايا جارس سوغاي بولوه وعددهم 42 معلما. وجدت الباحثة بأن المتعلم البطيء في المدرسة الابتدائية الدينية فايا جارس يواجهون الصعوبات في مهارة قراءة اللغة العربية. ومن أعظم الصعوبات التي يواجهها المتعلّم البطيء في القراءة هو الصعوبة عند قراءة الجملة الطويلة بطلاقة بسبب القدرة المعرفية المحدودة. هذه النتائج تدعم طرق التغلب على هذه الصعوبات هي تنظيم الأنشطة الإبداعية والنشطة التي تركز على الألعاب التّعليمية أو التّقنيات الأخرى بقدر الإمكان إذ أن المعلمين يلعبون دورا هاما في مساعدة المتعلمين البطيئين على تحسين مهاراتهم في قراءة باللغة العربية من خلال القيام بتقنيات مختلفة. This study aims to discover the difficulties of the slow learner in the skill of reading Arabic among primary school students, and at the same time focusing on the ways to overcome this problem. The researcher selected Sekolah Rendah Agama Paya Jaras as to discover the slow learner in a rural area which known to be located outside of the capitals and cities. The researcher follows the descriptive and analytical approach to the study of educational realities. The sample includes all 42 Malaysian teachers who teach in Sekolah Rendah Agama Paya Jaras, Sungai Buloh. The researcher found that slow learners in Sekolah Rendah Agama Paya Jaras had difficulties in reading Arabic. One of the greatest challenges faced by the slow learner in reading is the difficulty to read a long sentence fluently because of their limited cognitive ability. These findings support the ways to overcome the difficulties by organizing creative activities that focus on educational games or other techniques as much as possible. It shows that teachers play an important role in helping slow learners to improve their reading skills in Arabic by implementing different techniques.